Physiological and perceptual effects of precooling in wheelchair basketball athletes. (1st November 2016) - Forsyth, Peta; Pumpa, Kate; Knight, Emma; Miller, Joanna
Abstract : Objective : To investigate the physiological and perceptual effects of three precooling strategies during pre-exercise rest in athletes with a spinal cord injury (SCI). Design : Randomized, counterbalanced. Participants were precooled, then rested for 60 minutes (22.7 ± 0.2°C, 64.2 ± 2.6%RH). Setting : National Wheelchair Basketball Training Centre, Australia. Participants : Sixteen wheelchair basketball athletes with a SCI. Interventions : Participants were precooled through; 1) 10 minutes of 15.8°C cold water immersion (CWI), 2) ingestion of 6.8 g/kg −1 of slushie (S) from sports drink; 3) ingestion of 6.8 g/kg −1 of slushie with application of iced towels to the legs, torso and back/arms (ST); or 4) ingestion of 6.8 g/kg −1 of room temperature (22.3°C) sports drink (CON). Outcome measures : Core temperature (Tgi ), skin temperature (Tsk ), heart rate (HR), and thermal and gastrointestinal comfort. Results : Following CWI, a significant reduction in Tgi was observed compared to CON, with a greatest reduction of 1.58°C occurring 40 minutes post-cooling (95% CI [1.07, 2.10]). A significant reduction in Tgi following ST compared to CON was also observed at 20 minutes (0.56°C; [0.03, 1.09]) and 30 minutes (0.56°C; [0.04, 1.09]) post-cooling. Additionally, a significant interaction between impairment level and time was observed for Tgi and HR, demonstrating athletes with a higher level of impairment experienced a greater reduction in HR and significant decrease in rate of decline in Tgi, compared to lesser impaired athletes. Conclusion : CWI and ST can effectively lower body temperature in athletes with a SCI, and may assist in tolerating warm conditions.